Impact of heavy-flavour production cross sections measured by the LHCb experiment on parton distribution functions at low x - Zenaiev, O; Geiser, A; Lipka, K; Blümlein, J; Cooper-Sarkar, A; Garzelli, M; Guzzi, M; Kuprash, O; Moch, S; Nadolsky, P; Placakyte, R; Rabbertz, K; et al. (SpringerOpen, 2015)
The impact of recent measurements of heavy-flavour production in deep inelastic ep scattering and in pp collisions on parton distribution functions is studied in a QCD analysis in the fixed-flavour number scheme at next-to-leading order. Differential cross sections of charm- and beauty-hadron production measured by LHCb are used together with inclusive and heavy-flavour production cross sections in deep inelastic scattering at HERA. The heavy-flavour data of the LHCb experiment impose additional constraints on the gluon and the sea-quark distributions at low partonic fractions x of the proton momentum, down to x∼5×10−6 . This kinematic range is currently not covered by other experimental data in perturbative QCD fits.